2011
DOI: 10.1111/j.1600-051x.2011.01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial shifts during dental biofilm re-development in the absence of oral hygiene in periodontal health and disease

Abstract: Aim to monitor microbial shifts during dental biofilm re-development Methods Supra and subgingival plaque samples were taken separately from 28 teeth in 38 healthy and 17 periodontitis subjects at baseline and immediately after tooth cleaning. Samples were taken again from 7 teeth in randomly selected quadrants during 1, 2, 4 and 7 days of no oral hygiene. Samples were analyzed using checkerboard DNA-DNA hybridization. Species counts were averaged within subjects at each time point. Significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 26 publications
5
91
0
2
Order By: Relevance
“…These include hallmark pathogens, such as P. gingivalis and A. actinomycetemcomitans, as well as species associated with inflammation and enhancement of the pathogenic biofilm environment, e.g., Fusobacterium spp. (37,57). Thus, the bacterial ecologies in the mothers receiving a routine oral hygiene regimen were substantially different and reflected the distribution of bacteria normally associated with healthy biofilms in humans.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These include hallmark pathogens, such as P. gingivalis and A. actinomycetemcomitans, as well as species associated with inflammation and enhancement of the pathogenic biofilm environment, e.g., Fusobacterium spp. (37,57). Thus, the bacterial ecologies in the mothers receiving a routine oral hygiene regimen were substantially different and reflected the distribution of bacteria normally associated with healthy biofilms in humans.…”
Section: Discussionmentioning
confidence: 95%
“…We and others have shown that characteristics of the innate and humoral immune responses and the destruction of bone and connective tissue that accompany naturally occurring and ligature-induced periodontitis in Macaca fascicularis, Saimiri sciureus, Macaca nemestrina, Macaca mulatta, and Papio anubis parallel those observed in human periodontitis (5,6,(21)(22)(23). Nonhuman primate periodontal pockets are a habitat for a complex microbiota (18,20,(24)(25)(26)(27)(28) consisting of Gram-negative anaerobic species, such as Porphyromonas gingivalis (29)(30)(31), Treponema denticola (29,32,33), and Tannerella forsythia (29,34,35), similar to the microbial complexes identified in the subgingival biofilms of humans (36,37). Thus, there appears to be a relationship between the microbiological and immunological studies of gingivitis and periodontitis in humans and those which have been described for periodontitis in nonhuman primates.…”
mentioning
confidence: 99%
“…Conventional mechanical treatment and conventional homecare do not change the species of bacteria present before and after treatment [13]. Colombo et al, found mechanical therapy modestly decreased the mean counts of many of the recognized periodontal pathogens, but the counts of other suspected pathogens increased after treatment and the mean frequency of the reduced pathogens increased to base values by 9 months [14].…”
Section: Introductionmentioning
confidence: 99%
“…Homecare may not be able to reach subgingival biofilms around many implants 35 and homecare can be a contributing factor to bacteremia 36 . The remaining bacteria regrow and research has shown the subgingival biofilm recolonization is extremely diverse 37 .…”
Section: Introductionmentioning
confidence: 99%